Observational Study of Paclitaxel-Carboplatin versus Pemetrexed-Carboplatin for Advanced Pulmonary Adenocarcinoma at Single-Centre in Indonesia - Rianyta Rianyta; Melva Louisa; Elisna Syahruddin; Vivian Soetikno (eJournal Kedokteran Indonesia, 2021)
Platinum-based chemotherapy regimens with two types of drugs, such as paclitaxel-carboplatin and pemetrexedcarboplatin, are first-line therapy for pulmonary adenocarcinoma patients with negative epidermal growth factor receptor (EGFR) mutation. This study aimed to determine the efficacy, toxicity, and cost profile of paclitaxel-carboplatin compared to pemetrexed-carboplatin. This is a cross-sectional study. Pulmonary adenocarcinoma negative EGFR mutation naïve patients treated with paclitaxel-carboplatin or pemetrexed-carboplatin were included. Effectiveness was assessed based on the overall response rate (ORR) according to the response evaluation criteria in solid tumours (RECIST). A pharmacoeconomic analysis is performed based on clinical outcomes consisting of effectiveness and direct medical costs. Medical records from 21 patients with paclitaxel-carboplatin and 21 patients with pemetrexedcarboplatin were successfully evaluated. The effectiveness of the two chemotherapy regimens was not significantly different (OR, 1.25; 95% confidence interval, 0.34 to 4.64; p = 0.739). Frequent haematological toxicities experienced in the two groups were grade 1-2 anaemia, neutropenia, leukopenia. Grade 3 anaemia, leukopenia, and neutropenia were more common in the paclitaxel-carboplatin group. The two groups’ nonhematological toxicities were nausea vomitus and hair loss, with peripheral neuropathy more experienced by the paclitaxel-carboplatin group. Costminimization analysis reveals that the average cost per patient with pulmonary adenocarcinoma negative EGFR mutation with paclitaxel-carboplatin regimen was cheaper IDR 10,986,257.55 or 50.25%, compared to pemetrexedcarboplatin. In conclusion, there was no significant difference in the effectiveness of the two regimens. The most common adverse effects in both regimens were haematological toxicities. The average cost per patient with a paclitaxel-carboplatin regimen was cheaper compared to pemetrexed-carboplatin.